Ultrasonic estimation of gestation age in goats via placentomes diameter - Rasheed, Yaseen Mahmood (The Iraqi Journal of Veterinary Medicine, 2017)
The aim of the present study is to establish the relationship between gestational age and placentome measurement via real-time ultrasound. This study is conducted in the college of Veterinary Medicine at Diyala University. Seventeen multiparous does were synchronized for estrus and naturally served to obtain pregnancy and subsequently scanned using both transducers. Ultrasonic (U.S) examination was performed transabdominally (TA) with sector-probe (5MHz) and transrectally (TR) with linear-probe (7.5MHz), in 10 day interval done started from day 35-135 post mating. The placentome was observed for the first time on day 35 by using TR ultrasonic examination (7.5MHz) linear transducer, as echogenic densities on the surface of endometrium. The results showed a significant increased (P≤0.05) in placentomes growth with gestation age. The placentome diameter (PD) reached maximized size around days 126 (39.6±2.37mm). Also, the results indicated significant difference between placentome diameter (PD) size in single and twin-pregnant does at (P≤0.05). The average of PD size in the single and twin-pregnant does was, respectively, 7.5±0.41mm and 9.2±0.74 mm at the day 35 and 45 of gestation. The maximal size of PD was 39.2±2.50mm in singleton-bearing does during 116-125 day and 41.0±2.19 mm in twin-bearing does during 126-135 day of gestation. In conclusion, the determination of gestation age according to placentome measurement was not reliable after day 90. Also, the use of 7.5 MHz linear array transducer for TR examination was found to be efficient, for early recognition of placentomes starting point from 35 days of gestation, as well as, the larger placentomes are expected in twins-bearing does.